Activated carbon developed from orange peels: Batch and dynamic competitive adsorption of basic dyes - Fernandez, Maria Emilia (2014)
Activated carbon from orange (Citrus sinensis) peel was developed through H3PO4 acid activation. Its ability as an adsorbent for the removal of two representative basic dyes (methylene blue and rhodamine B) from single and binary dyes solutions in batch and continuous modes was examined. The orange peel-based activated carbon presented a high specific surface area (1090 m2/g), predominance of mesopores and acidic character. It also showed a high adsorption capacity for both dyes in batch and dynamic modes. Experimental equilibrium isotherms obtained from single-dye solutions fitted the Langmuir–Freundlich model, and those obtained from binary solutions were properly described by single and multi-component models. Breakthrough curves obtained from single-dye solutions exhibited a better removal performance for rhodamine B. Adsorption capacity at exhaustion time for this dye was 11% higher than for methylene blue. Additional experiments in dynamic conditions with a binary solution of both dyes pointed to adsorption competition for the active sites of the developed carbon. Breakthrough curves were adequately represented by a modified two-parameter model.